2013
DOI: 10.1186/1477-7819-11-168
|View full text |Cite
|
Sign up to set email alerts
|

Adenoma malignum of the uterine cervix: report of four cases

Abstract: Adenoma malignum (AM) of the cervix is a rare disease and it is difficult to diagnose due to the deceptively benign appearance of the tumor cells. These lesions have mucin-rich cystic lesions and are usually situated deep in the cervix. Since AM is very rare, standard screening tests, diagnostic tools and treatments have not yet been established. Radiologically, it mimics multiple nabothian cysts as a benign-looking tumor. Histologically, AM is a well-differentiated adenocarcinoma and could be misdiagnosed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Cystic mucinous adenocarcinoma is difficult to distinguish from other benign cystic lesions using conventional MR . Mucinous adenocarcinomas are neoplasms that arise from the endocervical glands, and a solid component and enhanced septum are the most commonly reported distinguishable features . However, from the cases reported in our study large tumor size and intracystic bleeding also constitute important supplemental features.…”
Section: Discussionmentioning
confidence: 64%
“…Cystic mucinous adenocarcinoma is difficult to distinguish from other benign cystic lesions using conventional MR . Mucinous adenocarcinomas are neoplasms that arise from the endocervical glands, and a solid component and enhanced septum are the most commonly reported distinguishable features . However, from the cases reported in our study large tumor size and intracystic bleeding also constitute important supplemental features.…”
Section: Discussionmentioning
confidence: 64%
“…Studies have reported an incidence of approximately 1% of all cervical adenocarcinomas. [1][2][3] This tumour has been described in several case series, and in these cases the most common symptoms were profuse mucinous vaginal discharge and vaginal bleeding. [2][3][4][5][6] This tumour has also been associated with Peutz-Jeghers syndrome (hereditary intestinal polyposis).…”
Section: Introductionmentioning
confidence: 95%
“…7,8 Other immunostains include carcinoembryonic antigen (CEA), MEC6, and p53, which are expressed in MDA and not expressed in normal cervix. HIK1083, although not commercially available, is specific for class III mucins of the stomach and may be positive in MDA; however, the sensitivity varies by study.…”
Section: Dear Editormentioning
confidence: 99%
“…HIK1083, although not commercially available, is specific for class III mucins of the stomach and may be positive in MDA; however, the sensitivity varies by study. 7,8 Other immunostains include carcinoembryonic antigen (CEA), MEC6, and p53, which are expressed in MDA and not expressed in normal cervix. These tumor cells are generally, negative for ER, PR, CA-125, and p16, although stromal positivity with ER and PR can be seen surrounding the lesion.…”
Section: Dear Editormentioning
confidence: 99%